Social expressions of Chinese university students: pragmatic failures and cultural differences / Wang Ningfang, Caesar Dealwis and John Francis Noyan - Ningfang, Wang; Dealwis, Caesar; Noyan, John Francis (Universiti Teknologi MARA, Sarawak, 2023)
Social language plays an increasingly important role in intercultural communication but the inaccurate use of social expressions will cause misunderstandings between the interlocutors that can lead to serious communicative conflicts and breakdowns. This paper examines the differences in the use of social expressions like greeting, parting, response to compliments, response to refusal and taking leave between Chinese and English languages, besides analysing the causes of these differences from the perspective of social values and criteria of politeness principles between Western countries and China. Drawing upon Brown and Levinson's Politeness Theory and Austin's Speech Act theory, the study investigates the social expressions in various speech acts performed by 150 Chinese undergraduates when coming into contact with English speaking foreigners in Ningxia Medical University through a closed-ended survey.